Abbreviating the Early Start Denver Model for community-based family-centered care - Vismara, Laurie A.; Nyugen, Lucy; McCormick, Carolyn E. B. (Frontiers in Psychology, 2023)
Introduction Parent-mediated approaches for young children with or with a higher likelihood of autism have gained traction, with mounting evidence of efficacy, but a research-to-gap practice exists, and community effectiveness remains to be firmly established. Methods Using a community-participatory framework, a total of 10 parent-child dyads received a five-day workshop and six follow-up sessions of ESDM parent coaching. Intervention was implemented across two phases with in-person and telehealth delivery. Results From pre to post intervention across both phases, parents improved in their fidelity of intervention implementation and children maid gains on proximal measures of social communication. Discussion Community delivery of an evidence-based parent-mediated interventions for toddlers on the autism spectrum is feasible and promising. Giving resource efficiencies associated with parent-mediated approaches, particularly when delivered through government-funded programs, findings bolster current efforts to promote earlier and more widespread community access to necessary interventions. Facilitators and barriers to supporting parent learning and behavior change via interactive strategies are discussed.